Status fisiologi dan pertambahan bobot badan kelinci jantan lokal lepas sapih pada perkandangan dengan bahan atap dan ketinggian kandang berbeda - Ita Wahyu Nursita; Nur Cholis; Arie Kristianti (Faculty of Animal Science, Universitas Brawijaya, 2013)
To know the effect of cage roof materials and the height of cage to the physiology status and body weight gain of the experiment were done to 36 Local male rabbit at post weaning (6-8 weeks of age) with average initial weight of 630-1100g for three months in Field Laboratorium Sumber Sekar Dau Malang. The treatment given was cage roof material (tile vs zinc roof) and the height of the cage (30, 80 or 130 cm). The animals were caged individually in random. The feed given was foliage (col leaves) (at 03.00 pm) and pollard (at 07.00 am). The design used was Nested Design. The variables measures were rectal temperature ( oC), the frequency of respiration (/minute), heartbeats (/minutes), total feed consumption (g) and body weight gain (g). The obtained data then analysed statistically using variance and covariance test, if there was significant effect then continued by Duncan test. There were no significant effect of the treatment to the physiolgical status of the animals, except fr the heartbeats. There was no continue result between the increase of the height of the cage and the decrease of the heartbeat, except for the zinc roof. In the tile roof, the body weight gain was lower for the higher height of the cage, except for the tile roof of 130 cm height of the cage. These treatment combination gave the highest total feed consumption and body weight gain.Based on the result, it can be concluded that the tile roof materials with the height of the cage of 130 cm give good result, by improving total feed consumption, body weight gain and normal physiological status. Keywords: physiology status, body weight gain, rabbit